A diclofenac suppository–nabumetone combination therapy for arthritic pain relief and a monitoring method for the diclofenac binding capacity of HSA site II in rheumatoid arthritis. (24th January 2013) - Setoguchi, Nao; Takamura, Norito; Fujita, Ken‐ichi; Ogata, Kenji; Tokunaga, Jin; Nishio, Toyotaka; Chosa, Etsuo; Arimori, Kazuhiko; Kawai, Keiichi; Yamamoto, Ryuichi
ABSTRACT Diclofenac suppository, a non‐steroidal anti‐inflammatory drug (NSAID), is used widely in rheumatoid arthritis (RA) patients with severe arthritic pain. As the binding percentage of diclofenac to serum proteins is high, its free (unbound) concentration after rectal administration is low. To increase temporarily the free concentration of diclofenac and to enhance its analgesic effect by inhibiting the protein binding of diclofenac, the analgesic effect of diclofenac was examined before and after the start of an inhibitor administration to RA patients with insufficient control of arthritic pain, and the protein binding capacity of diclofenac was evaluated. Binding experiments were performed by ultrafiltration, and arthritic pain was recorded by the face scale. Free fractions of diazepam and diclofenac were augmented by increasing 6‐methoxy‐2‐naphthylacetic acid (6‐MNA; the active metabolite of the NSAID nabumetone) concentrations. The free fraction of diazepam increased after the start of nabumetone administration to RA patients, and arthritic pain relief was observed. These results suggest that 6‐MNA has an inhibitory effect on the protein binding of diclofenac and the free fraction of diazepam can be used to evaluate the binding capacity of diclofenac. It is considered that diclofenac suppository–nabumetone combination therapy and the method for protein binding monitoring by diazepam can positively benefit RA patients with insufficient control of arthritic pain. Copyright © 2013 John Wiley & Sons, Ltd.